2011
DOI: 10.3109/09638288.2010.546937
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural validation of the Falls Efficacy Scale International (FES-I) in Greek community-dwelling older adults

Abstract: The Greek FES-I was valid, reliable, comprehensible and acceptable for the sample tested and may thus, be used in cross-cultural rehabilitation research and practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
68
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 61 publications
9
68
2
1
Order By: Relevance
“…Lomas-Vega, HitaContreras, Mendoza, & Martínez-Amat, (2012) validated the FES-I in a sample of postmenopausal women, but studies are needed to confirm its validity for the global population. The fact that this has been done in many other languages such as Dutch, German, English and, more recently, Greek, Chinese or Turkish (Billis et al, 2011;Kwan et al, 2013;Ulus et al, 2012), suggests that it can very probably also be validated in Spanish, as it is a solid and consistent test irrespective of culture or language.…”
Section: P-valuementioning
confidence: 97%
“…Lomas-Vega, HitaContreras, Mendoza, & Martínez-Amat, (2012) validated the FES-I in a sample of postmenopausal women, but studies are needed to confirm its validity for the global population. The fact that this has been done in many other languages such as Dutch, German, English and, more recently, Greek, Chinese or Turkish (Billis et al, 2011;Kwan et al, 2013;Ulus et al, 2012), suggests that it can very probably also be validated in Spanish, as it is a solid and consistent test irrespective of culture or language.…”
Section: P-valuementioning
confidence: 97%
“…To assess the test-retest reliability (in repetitive measurements), an initial assessment and a re-assessment, approximately at the same time and under the same conditions took place in a time frame of 7 to 10 days as similar research had followed (Godi et al, 2013;Βillis et al, 2011). The inter-rater reliability was used to assess the agreement between the grades given by the two raters (Ouzouni and Nakakis, 2011).…”
Section: Reliability Assessmentmentioning
confidence: 99%
“…Reliability in total scores also agrees with the study of Dahl and Jørgensen (2014) in stroke patients, even though in their study each patient was assessed by 3 examiners, which provides an advantage compared to our study; and the reassessment took place after 4 weeks compared to the 7-10 days timeframe of our study. The use of two examiners and assessement based on live observation instead of observation of video recordings in our study was chosen because of being a commonly used methodological procedure for this kind of research, and of being a common way of assessment in clinical settings (Löfgren et al, 2014; Maia, Rodrigues-de-Paula, Magalhães, and Teixeira, 2013; Tsang, Liao, Chung, and Pang, 2013;Βillis et al, 2011). Furthermore, a relatively big interval between the two assessments was not considered as methodologically correct for our study, given that 4 weeks is enough time for alterations in the environment or health status, and eventually in the performance of the participant to occur.…”
Section: Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…In numerous studies it was found that one of the main risk factors for falling is at least one previous fall [13,25]. Fear of falling is claimed by 29-92% of the elderly who had one or more falls [26].…”
Section: Discusionmentioning
confidence: 99%